The role of digital tourism destination in achieving digital tourism destination performance through digital's role as intervening variables - Zahera Mega; Jubery Marwan (IJHCM (International Journal of Human Capital Management), 2022)
ABSTRACT The purpose of this study is to determine and analyze the role of digital tourism destinations in realizing the performance of digital tourism destinations through the role of digital as an intervening variable. This research approach is quantitative with the type of explanatory research. Sources of primary data were obtained using the survey method. This research was conducted in the Thousand Islands Regency, Jakarta before the Covid-19 period. Researchers have surveyed as many as 140 people to tourism actors, but from 140 people who meet the requirements 100 samples. To test the hypothesis using path analysis. The research findings show that: (1) digital tourism destination variables (destination image, accessibility, infrastructure, and travel agency) affect the digital role; (2) digital tourism destination variables (destination image, accessibility, infrastructure, and travel agency) do not directly affect digital tourism destination performance; (3) Digital tourism destination variables (destination image, accessibility, infrastructure, and travel agency) through digital roles affect digital tourism destination performance. The results of the analysis show that; (1) The success of digital technology that plays a role in providing tourism information contributes to providing a platform on digital technology as a form of providing information for potential tourists, this is effective because the millennial generation relies on various popular platforms that are commonly used in finding tourism information, and have met the criteria basic needs of life before tourism activities are carried out. The ability to share and exchange information between tourism providers and prospective tourists freely has an impact on increasing the number of tourists who; (2) The role of digital is used as a promotion in attracting tourists to visit using; formation of a positive destination image opinion, the availability of good accessibility including modes of transportation; infrastructure, tourist attraction areas that have added value, good travel agency services, so that the final impact can contribute to increasing the number of tourists. The ability to share and exchange information between tourism providers and potential tourists freely has an impact on digital tourism destination performance. Keywords: Digital tourism destination, Digital tourism destination Performance, and Digital Role.